Femoroacetabular Impingement Syndrome in the Athletic Population: From Morphology to Return to Sport - Tłoczek, Wiktoria; Twardowska, Daria; Śliwa, Wiktoria; Jelonek, Barbara; Tomczak, Barbara; Porada, Dagmara; Żukowiecka-Sęga, Dominika; Wandzel, Małgorzata; Topolski, Kamil; Klubikowska, Karolina (Quality in Sport, 2026)
Background: Femoroacetabular impingement syndrome (FAIS) is a recognized cause of hip pain and functional limitation, particularly in young and physically active individuals. The condition results from abnormal hip morphology leading to mechanical conflict within the joint and is associated with an increased risk of early hip osteoarthritis. Although awareness is rising, key aspects of the disease in athletes remain unclear. Aim: The aim of this study was to review current evidence regarding the epidemiology, risk factors, pathophysiology, clinical presentation, diagnostic strategies and treatment options for FAIS with particular emphasis on athletes. Material and methods: The review of the literature was conducted using available studies concerning FAIS in the PubMed database. Peer-reviewed articles published in English were analyzed, including in the fields of orthopedics, sports medicine and musculoskeletal imaging. Results: FAIS predominantly affects young athletes involved in high-demand sports requiring repetitive hip flexion and rotation. Cam morphology is common in males and appears to develop during skeletal immaturity under repetitive mechanical loading. Diagnosis requires a combination of symptoms, positive clinical tests and imaging-confirmed morphological abnormalities. Nonoperative management can alleviate symptoms in selected patients, however arthroscopic surgery has demonstrated superior outcomes. Return to sport rates after arthroscopic management are generally high, although return to pre-injury performance levels varies. Conclusions: FAIS is a multifactorial condition with significant clinical implications for young and athletic populations. Early recognition, accurate diagnosis with individualized treatment strategies are essential to optimize functional outcomes and delay degenerative joint changes. Further high-quality, sport-specific research is needed to refine prevention strategies and improve long-term outcomes, particularly in athletes.